2011
DOI: 10.1021/jf202584b
|View full text |Cite
|
Sign up to set email alerts
|

Development of Flexible Antimicrobial Packaging Materials against Campylobacter jejuni by Incorporation of Gallic Acid into Zein-Based Films

Abstract: In this study, antimicrobial films were developed against Campylobacter jejuni by incorporation of gallic acid (GA) into zein-based films. The zein and zein-wax composite films containing GA between 2.5 and 10 mg/cm 2 were effective on different C. jejuni strains in a concentration-dependent manner. Zein and zein-wax composite films showed different release profiles in distilled water but quite similar release profiles at solid agar medium. Depending on incorporated GA concentration, 60À80% of GA released from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 38 publications
(65 reference statements)
5
51
0
Order By: Relevance
“…However, the composites and blend films are still much more flexible than the controls. This result confirmed the recent findings of Alkan et al (2011) who tested mechanical properties of zein and zein-wax composites containing gallic acid. Fabra, Talens, and Chiralt (2008) also reported reduction in elongation of wax containing caseinate films and attributted this effect to discontinuities in the polymer network by the incorporated waxes.…”
Section: Mechanical Properties Of Filmssupporting
confidence: 92%
See 1 more Smart Citation
“…However, the composites and blend films are still much more flexible than the controls. This result confirmed the recent findings of Alkan et al (2011) who tested mechanical properties of zein and zein-wax composites containing gallic acid. Fabra, Talens, and Chiralt (2008) also reported reduction in elongation of wax containing caseinate films and attributted this effect to discontinuities in the polymer network by the incorporated waxes.…”
Section: Mechanical Properties Of Filmssupporting
confidence: 92%
“…Effects of plasticizer catechin on lysozyme release profiles of films Arcan and Yemenicioglu (2011) have recently found that some phenolic compounds including catechin can be used effectively as natural plasticizer for zein films which has commercialization problems as self-standing films due to their brittleness and lack of flexibility. The interaction of hydroxyl groups of phenolic compounds with carbonyl groups of zein biopolymer creates a plasticizing effect and causes modifications in film morphology depending on the molecular properties of phenolic compounds (Alkan et al, 2011;Arcan & Yemenicioglu, 2011). The major morphological change caused by catechin in zein films is the reduced film porosity (Arcan & Yemenicioglu, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the some of the CD molecules located on the fiber surface whereas some CD molecules are buried in the bulk of the fiber matrix. Zein is a useful food packaging material (Alkan et al, 2011;Shi et al, 2009), and CDs have inclusion complexation capability with variety of molecules including aromas, colors, antioxidants, antibacterials, odors, and other functional ingredients (Del Valle, 2004;Hedges, 1998;Szejtli, 1998), therefore, zein/CD nanofibers may have the potentials to be used as active food packaging (López-de-Dicastillo, Gallur, Catalá, Gavara, & Hernandez-Muñoz, 2010; López-de-Dicastillo, Jordá-Beneyto, Catalá, Gavara, & HernandezMuñoz, 2011) materials owing to surface associated CD molecules and their high surface areas.…”
Section: Surface Characterization Of Zein/cd Nanofibersmentioning
confidence: 99%
“…Zein films and zein micro/nano particles can be used for encapsulation of essential oils, aromas and flavors, controlled release of active additives and as an active food packaging material, etc. (Alkan et al, 2011;Parris, Cooke, & Hicks, 2005;Patel, Heussen, Hazekamp, Drost, & Velikov, 2012;Sanchez-Garcia, Hilliou, & Lagaron, 2010;Shi, Kokini, & Huang, 2009;Zhong, Jin, Davidson, & Zivanovic, 2009). In the recent years, electrospinning of zein nanofibers have received much attention as well (Jiang, Reddy, & Yang, 2010;Jiang & Yang, 2011;Jiang, Zhao, & Zhu, 2007;Miyoshi, Toyohara, & Minematsu, 2005;Selling et al, 2007Torres-Giner, Gimenez, & Lagaron, 2008;).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the solubility for the gallic acid treated films can be attributed to the high number of hydroxyl groups in gallic acid as well as the inherent property of gallic acid of being soluble in water. Some authors have previously reported that depending on incorporated gallic acid concentration, 60-80 % was released from the films, while the remaining gallic acid was trapped in the film matrix (Alkan et al 2011). It was observed (data not shown) that the fraction less than 180 Da which covered the gallic acid had the highest concentration after gallic acid treatment (56 % for the gallic acid treated film solution against 22 % for the control) suggesting that gallic acid was retained and considering the hydrophilic nature of gallic acid, this might probably be the reason for the increased solubility from the presumed trapped gallic acid in the film matrix.…”
Section: Effect Of Gallic Acid On Thickness Moisture Content and Solmentioning
confidence: 99%